Isolation and identification of spore associated bacteria (SAB) from Glomus and Gigaspora spp. in coconut and arecanut based cropping systems - Ambili, K.; Thomas, George V.; Indu, P.; Viji, M.V.; Gopal, Murali; Gupta, Alka (Journal of Plantation Crops, 2012)
Arbuscular mycorrhizal symbiosis is exhibited by 80% of the terrestrial plants. The spores of arbuscular mycorrhizal fungi (AMF) form a unique microhabitat for the colonization by many species of bacteria. The present study was undertaken to isolate and identify spore associated bacteria (SAB) and evaluate their functional role in AMF-host interactions with respect to germination of spores. Coconut and arecanut based cropping systems under organic management practices in farmer’s field in Kasaragod district, Kerala and high density multi species cropping system (HDMSCS), CPCRI farm were selected for the study. The results revealed that AMF spore load of a particular cropping system increase with the number of intercrops. Spore associated bacteria (SAB) were isolated from the cytoplasm of surface sterilized spores of Glomus and Gigaspora spp. Identification based on BIOLOG and 16S rRNA sequencing revealed the presence of bacteria - Citrobacter amalonaticus, Staphylococcus arlettae, Bacillus subtilis, Bacillus amyloliquefaciens, in association with spores of Glomus spp. Corynebacterium coyleae, Bacillus cereus and Bacillus subtilis were found to be associated with Gigaspora spp. In vitro studies to determine the germination potential in spores showed the maximum results with Bacillus cereus GiPHD1 and Citrobacter amalonaticus GLNCB1 with 40% increase over control.